Analisis Masalah dan Solusi Prioritas Pengembangan UMKM - Septiana, Nurul Izzati; Rozi, A. Fahrur; Muar, Romli (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2019)
This research is a qualitative-quantitative analysis that aims to capture a value or view represented by experts and practitioners about problems, solutions, and strategies for developing SMEs in Palaan village. The analytical tool used is the ANP method and is processed using the "Super Decision" software. The selection of respondents in this study was conducted using a purposive sample by considering the respondent's understanding of the problems, solutions, and strategies for the development of SMEs in Palaan Village, Malang Regency. The problems and solutions that occur from the development of MSMEs in Palaan Village in order of priority are marketing problems, product development quality problems, and capital problems. Recommendations from this study require further research on the study of conceptual details of the solutions offered for the development of MSMEs.